2007
DOI: 10.1155/2007/64012
|View full text |Cite
|
Sign up to set email alerts
|

The Shooting Method and Nonhomogeneous Multipoint BVPs of Second-Order ODE

Abstract: Recommended by Kanishka PereraIn a recent paper, Sun et al. (2007) studied the existence of positive solutions of nonhomogeneous multipoint boundary value problems for a second-order differential equation. It is the purpose of this paper to show that the shooting method approach proposed in the recent paper by the first author can be extended to treat this more general problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…The existence of positive solutions of BVPs with nonlocal BCs, including three-point, multi-point, and integral BCs, have been studied extensively, see, for example, [1,4,5,6,7,8,9,15,16,24,26,28,29,31] and the references therein. In recent years, progress has also been made to the study of nodal solutions, i.e., solutions with a specific zero-counting property in (a, b), for nonlinear BVPs consisting of Eq.…”
Section: −(P(t)ymentioning
confidence: 99%
“…The existence of positive solutions of BVPs with nonlocal BCs, including three-point, multi-point, and integral BCs, have been studied extensively, see, for example, [1,4,5,6,7,8,9,15,16,24,26,28,29,31] and the references therein. In recent years, progress has also been made to the study of nodal solutions, i.e., solutions with a specific zero-counting property in (a, b), for nonlinear BVPs consisting of Eq.…”
Section: −(P(t)ymentioning
confidence: 99%
“…(1.4) Under some assumptions, it was shown that there exists λ * > 0 such that BVP (1.3), (1.4) has at least one positive solution for 0 < λ < λ * and has no positive solution for λ > λ * . Later on, in [6,10,11,[13][14][15][16], this result was generalized to other problems with a parameter λ in the BCs. Here, we mention that, in all of the above work, neither the uniqueness of solutions nor the dependence of solutions on the parameter λ is studied, and only papers [10,11,16] studied the multiplicity of solutions.…”
Section: Introductionmentioning
confidence: 95%
“…To some extent, this approach has an advantage over the traditional methods. Readers can see [11][12][13][14][15][16] and the references therein for details.…”
Section: Introductionmentioning
confidence: 99%